The Controlling Aedes Aegepty Mosquitoes as Dengue Fever Vectors Using 3M Poster Media for Junior High School Students of the Mutiara Aulia Education Foundation - Ashar, Yulia Khairina; Sibarani, Adinda Riskiya; Nasution, Amalia Rahmi; Rizki, Aprida Aulia; Nathasyah, Diva Aulia; Rizqika, Indah; Syahputri, Nuri Nabila (Tadulako University, 2025)
Dengue Hemorrhagic Fever (DHF) is still a serious health problem in Indonesia, with 210,644 cases and 1,239 deaths reported until the 43rd week of 2024. One of the causes is the activity of disease vectors that bite in the morning and afternoon which can occur when children are at school. This study aims to determine the effect of counseling on increasing students' knowledge about prevention and control of DHF disease vectors at Mutiara Aulia Middle School. This study used an experimental method with a Pre- Experimental (non-designs) design of the One-Group Pretest-Posttest Design . The study population was all students of Mutiara Aulia Middle School with a sample of 63 people. Based on the research that has been carried out, the results found that the average pre-test was 52.42 and the average post-test was 80.06, which means that there was an increase in knowledge. The results also show that the significance value is 0.000 (<0.05), this means that knowledge before and after counseling is not the same. then there is a significant difference. So it can also be concluded that there is an increase in knowledge and insight of students at MIS Mutiara Aulia school about Controlling Aedes Aegepty Mosquitoes as Vectors of Dengue Fever . It is expected that MIS Mutiara Aulia students can apply the knowledge gained in everyday life.